Enhancement of ferromagnetism in a multiferroic La–Co co-doped BiFeO3 thin films. (1st September 2022) - Song, Shaoqing; Jia, Longfei; Wang, Shuolin; Zheng, Dahuai; Liu, Hongde; Bo, Fang; Kong, Yongfa; Xu, Jingjun
Abstract: BiFeO3 -based materials have attracted considerable attention owing to their room-temperature multiferroic properties and ultrahigh ferroelectric polarization. In this study, La and Co co-doped BiFeO3 (BLFCO) thin films were fabricated on Pt (111)/Ti/SiO2 /Si substrate buffered by Nb-doped (0.7 wt.%) SrTiO3 via pulsed laser deposition. Experiments revealed that the film deposited at 0.2 Pa comprised the predominant orientation of BiFeO3 (BFO) (111), and its surface root-mean-square roughness was 0.96 nm. The saturation magnetization of the film reached 25.3 emu cm 3, which was an order of magnitude higher than that of the pure BFO film, as well as the remanent magnetization reached 1.8 emu cm −3 . The result was attributed to the predominant orientation and small grain size of BLFCO films. The piezo-response force microscopy measurements revealed the co-doped film possesses well repeatable performance of polarization reversal, and the presence of ferroelectric orders with an asymmetric 'butterfly' structure. These results are helpful for further improving the performance of BFO multifunctional devices.